Investigating learner attitudes toward mobile learning environments: Based on gender perspectives - Liaw, Shu-Sheng (International Dialogues on Education Journal, 2015)
Mobile technology, accessing Internet resources anytime and anywhere, empowers the shift from traditionally pure instructor-centered classroom teaching to fully learner-centered educational settings. On the other hand, the issue of the relationship between gender perspectives and mobile learning environments has been a controversial topic in educational technology. Therefore, the main research objective of this study is to explore gender perspectives of attitudes toward mobile learning environments. Subjects of the study were selected university students who had already used an APP-based m-learning system for a month. A total of two hundred thirty-three valid questionnaires were collected, spilt evenly between female and male students. Based on gender perspectives, our statistical analyses lead to various significant conclusions.